A Two Years Study on Pregnant Women with Cardiac Disease in a Tertiary Care Centre - Sayeeda, Syeda; Wahid, Fatima; Begum, Firoza; Zaman, Mahboob Mustafa (Bangladesh Journal of Obstetrics & Gynaecology, 2009)
Objective: To analyse the pregnant women with heart disease and to assess its influence on the fetomaternal outcome. Materials and methods: This observational study was carried out during the period from Jan 2006 to Sept 2007. Fifty pregnant women with cardiac diseases who were admitted in the Fetomaternal Medicine unit of the department of Obstetrics & Gynaecology in Bangabandhu Sheikh Mujib Medical University (BSMMU) were included in the study. Results: Rheumatic heart disease (n-37, 74%) with isolated mitral stenosis (28%) was the predominant cardiac problem among the study subjects while atrial septal defect (16%) was the most common form of congenital heart disease (n-13, 26%). Based on New York Heart Association (NYHA) functional classification, 40(80%) women were in class-I, 7(14%) were in class-II and 3(6%) were in class-III heart disease on presentation. The mean (±SD) gestational age at delivery was 37.50(±2.50) weeks and pregnancy duration was shortened in more advanced classes of heart disease. The rate of cesarean section (90%) was high in the study subjects. The rate of prematurity (55.5%) was high among class II and III and average birth weight of neonates were less among these two classes compared to class I (2.80±0.20 kg in Class-I, 2.30±0.26 in Class-II and 2.10±0.34 in Class-III). No baby was delivered stillborn and there was no neonatal death. Out of fifty, nine patients developed heart failure during the hospital stay. Duration of hospital stay was shorter in class-I (7.50±1.50) and was prolonged in more advanced classes of heart disease (9.50±1.56 in Class-II and 13.80±4.20 in Class-III). Two patients of the study subjects expired. Conclusion: Rheumatic heart disease was the predominant type of heart disease in pregnancy and most of the women were in class I on admission. The neonatal outcome was satisfactory. Two patients in the congenital heart disease group expired during the study period. Key words: Maternal, Fetal, Cardiac disease. doi: 10.3329/bjog.v23i1.3050 Bangladesh J Obstet Gynaecol, 2008; Vol. 23(1) : 3-7